Historical traditions of Moscow urban planning in the development of low-rise buildings - Ustinov Ivan Aleksandrovich (E3S Web of Conferences, 2023)
At present, it is necessary to preserve the scale of the existing urban environment, accounting for the accumulated urban planning experience and existing historical traditions. This will enable to find flexible urban planning solutions providing modern infrastructure for low-rise development in historically formed areas of the city and territories with special status. By the middle of the XIX century, Moscow residential development had represented two morphotypes: old low-rise sparse and low-rise perimeter, a consequence of the peculiarities of Muscovite life. The third morphotype, formed under the influence of the first two, was represented by individual architectural projects realized in the 1940s 1950s. Today, the concept of the private urban house with a homestead plot is still relevant. Townhouse is a form of urban dwelling with a small backyard. This form is a flexible entity combining the qualities of an urban house integrated into the urban system and a low-rise structure. Low-rise development retains an established historic scale whereas the historic fabric of the city remains unified and harmonious. Scale with historical architecture enables to integrate townhouses in the historically established areas of the city, without destroying formed city fabric. Townhouse fits into the natural landscape more harmoniously, continuing the tradition of the city and developing surrounded by gardens and parks.